Analisis Implementasi Pembelajaran IPS Berbasis Digital terhadap Keterlibatan Siswa Sekolah Dasar: Studi Kasus di Kelas IV SD Negeri 04 Sikabu Kabupaten Agam - Hafidza, Ummul; Suci Andesta; Adrias, Adrias; Azmi Alwi, Nur (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
his study aims to analyze the implementation of digital-based Social Studies (IPS) learning and its relationship with student engagement in elementary school. The research employed a descriptive qualitative approach supported by simple quantitative data. The subjects of this study were a fourth-grade teacher and students at SD Negeri 04 Sikabu, Agam Regency. Data collection techniques included observation, interviews, and questionnaires. Data were analyzed descriptively through data reduction, data display, and conclusion drawing. The results showed that digital-based IPS learning was implemented effectively through the application of Problem Based Learning (PBL) and Project Based Learning (PJBL), supported by digital media such as learning videos, PowerPoint presentations, and Quizizz applications. The learning process was active, contextual, and able to enhance student engagement. Questionnaire results indicated a percentage of 85.83% in the very high category, showing that students responded positively to digital-based learning. However, several challenges were identified, including limited technological facilities, unstable internet access, and differences in student abilities. Therefore, differentiated learning strategies and optimization of instructional media are needed to improve the effectiveness of the learning process. In conclusion, digital-based IPS learning has a positive contribution to improving student engagement in elementary schools.